Analysis of challenges, costs, and governance alternative for peatland restoration in Central Kalimantan, Indonesia - Puspitaloka, D.; Kim, Y-S.; Purnomo, H.; Fulé, P.Z. (Elsevier, 2021)
Restoration of degraded tropical peatland is considered to be one of the most cost-efficient measures in reducing greenhouse gas emissions and conserving biodiversity. Although benefits of restoration are often expected to substantially exceed the costs, most restoration projects are being carried out without clear cost analyses. This study provides empirical assessments of challenges and costs of the four peatland restoration projects managed by different proponents in Central Kalimantan, Indonesia based on key informant interviews, a follow-up survey and document analyses. We also reviewed existing policy contexts that can address some of the challenges to propose a governance alternative to sustain peatland restoration efforts. We found that many ecological challenges of peatland restoration projects were created by drainage canals leaving the peat to be dry and fire prone. Peatland degradation has been exacerbated by human activities and human-caused fires, and restoration efforts have faced many challenges due to lack of secure funding and complexity of governing the project implementation. The key informants we interviewed easily recognized direct costs for implementing restoration activities, but often left out indirect costs of addressing social challenges, such as expenses to engage local communities, in their assessments of the costs. Although our accounting is far from exhaustive, we found that indirect costs can add up to half of the total cost of peatland restoration projects. Current funding mechanisms for these projects mostly rely on international donors and private sectors, which make the long-term sustainability of the projects questionable. We argue that hybrid governance for a green business model, such as restoration and ecosystem services enterprises, with active participation from the public sector should be mainstreamed. The accounting framework developed in this study can be applied in other projects and should be further revised to systematically assess cost-effectiveness of restoration interventions.